Energy Economics - Zweifel, Peter; Praktiknjo, Aaron; Erdmann, Georg (Springer, 2017)
Access to energy resources, energy supply security, high and increasing prices of energy, lack of competition, slow market entry of renewables, insufficient investment in energy efficiency, and sluggish progress in reducing greenhouse gas emissions are all well-known issues and concerns characterizing energy markets. Yet, what are the possibilities of finding effective, efficient, and sustainable solutions to these problems? The fundamental claim of this book is that solutions cannot be found without an in-depth analysis of energy markets that acknowledges not only their physical and technological constraints but also their structural idiosyncrasies and the behavior of market participants. This text is the result of 30 years of teaching and research performed by the authors at both German- and English-speaking universities in Europe. It therefore adopts a distinctly European approach, yet without neglecting developments worldwide. While firmly anchored in economic theory, it also presents empirical evidence enabling readers to assess the relevance of predicted relationships. For instance, it is certainly of interest to know that the so-called elasticity of substitution is a crucial parameter for answering the question whether man-made capital can replace energy quickly enough to assure sustainability in terms of consumption in spite of the fact that energy constitutes an ultimately limited resource. In addition, it is also important to see whether the estimated elasticities of substitution are typically below one (making sustainability questionable) or above one (suggesting sustainability can be attained).
Theory and Applications